1991
DOI: 10.1073/pnas.88.7.2820
|View full text |Cite
|
Sign up to set email alerts
|

Direct photoaffinity labeling of tubulin with colchicine.

Abstract: Ultraviolet irradiation of the [3Hjcolchicine-tubulin complex leads to direct photolabeling of tubulin with low but practicable efficiency. The bulk (70% to >90%) of the labeling occurs on (8-tubulin and appears early after irradiation, whereas a-tubulin is labeled later. The labeling ratio of .8-tubulin to a-tubulin (13/a ratio) is reduced by prolonged incubation, prolonged irradiation, urea, high ionic strength, the use of aged tubulin, dilution of tubulin, or large concentrations of colchicine or podophyllo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 29 publications
3
45
0
Order By: Relevance
“…In late stages of irradiation, or with "damaged" tubulin, label also appeared in a-tubulin (9). These results suggested the possibility that the colchicine-binding domain on 3-tubulin might be near a-tubulin.…”
Section: Example Low-mentioning
confidence: 53%
See 1 more Smart Citation
“…In late stages of irradiation, or with "damaged" tubulin, label also appeared in a-tubulin (9). These results suggested the possibility that the colchicine-binding domain on 3-tubulin might be near a-tubulin.…”
Section: Example Low-mentioning
confidence: 53%
“…Whether these bands are precursor peptides or provide other binding surfaces remains to be determined. Moreover, the region of a-tubulin that is near enough to the colchicine-binding site on ,B-tubulin to become labeled under mild denaturing conditions (6,9,10) remains to be identified. Nonetheless, our findings identify two regions of 3-tubulin that are important structural elements of the colchicine-binding site.…”
Section: Resultsmentioning
confidence: 99%
“…By direct photoaffinity labeling with vinblastine (17) and with two photoactive derivatives of vinblastine (18,19), there was greater labeling of ␣-tubulin than ␤-tubulin, ranging from 57 to 75% of the incorporated radiolabel being in the ␣-subunit. A photoaffinity analog of maytansine was incorporated in about a 4:5 ratio into ␣-and ␤-tubulin, respectively (20).…”
mentioning
confidence: 99%
“…In spite of the intensive study of colchicine-tubulin interaction, there is no consensus about the location of the colchicine binding site on tubulin. Some studies have placed the colchicine binding site on the a subunit [2], some on the p subunit [3] and some at the interface [4].Luduena and co-workers [5] have used cross linkers to crosslink two sulfhydryl groups which are at the colchicine binding site. They have shown that these two sulfhydryl groups are protected from chemical modification by colchicine and its analogs and identified them as Cys239 and Cys354 of the p subunit [6, 71.…”
mentioning
confidence: 99%
“…In spite of the intensive study of colchicine-tubulin interaction, there is no consensus about the location of the colchicine binding site on tubulin. Some studies have placed the colchicine binding site on the a subunit [2], some on the p subunit [3] and some at the interface [4].…”
mentioning
confidence: 99%